2022
DOI: 10.3390/jcp2030033
|View full text |Cite
|
Sign up to set email alerts
|

Security and Privacy Management in Internet of Medical Things (IoMT): A Synthesis

Abstract: The Internet of Medical Things (IoMT) has become a strategic priority for future e-healthcare because of its ability to improve patient care and its scope of providing more reliable clinical data, increasing efficiency, and reducing costs. It is no wonder that many healthcare institutions nowadays like to harness the benefits offered by the IoMT. In fact, it is an infrastructure with connected medical devices, software applications, and care systems and services. However, the accelerated adoption of connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…However, if there is more than one, the best solution is selected when the search agent's position is modified using Eq (15). The inertia weight is changed in the next stage using Eq (13). The next stage involves updating the position and velocity parameters in the APSO-CNN using Eqs (11) and (12).…”
Section: As Illustrated Inmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if there is more than one, the best solution is selected when the search agent's position is modified using Eq (15). The inertia weight is changed in the next stage using Eq (13). The next stage involves updating the position and velocity parameters in the APSO-CNN using Eqs (11) and (12).…”
Section: As Illustrated Inmentioning
confidence: 99%
“…Following the spread of COVID-19, it was found that 71% of security specialists believe that security vulnerabilities in IoT networks are increasing [10,11]. Some studies [12][13][14] describe the attacks and security vulnerabilities of each IoT layer and suggest ways to protect privacy [15][16][17]. Attacks on Internet of Things devices have increased and several studies have developed intrusion detection systems [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ransomware attacks are rapidly growing and are threats to individuals, businesses, and government and private sectors, where the attackers infect their deployed infrastructure and demand large amounts of ransom [ 8 , 9 , 10 ]. Due to an excess of such attacks, newer versions of the ransomware attacks appear frequently and have been responsible for millions of dollars of losses annually [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, IoMT can assist with the requirement of more genericity and scalability [1]. Many healthcare practitioners use IoMT applications to improve therapy, disease control, failure reduction, drug prescription management, and cost savings [3]. Furthermore, IoMT tremendously advances healthcare systems by expediting procedures that enable the adoption of cutting-edge diagnostic and therapeutic techniques via connected wearable sensor devices and real-time monitoring data available from IoT technologies [4].…”
Section: Introductionmentioning
confidence: 99%